Analisis Faktor Yang Mempengaruhi Motivasi Siwa Mengikuti Kegiatan Pramuka Kelas VIII di MTsN 2 Pasaman Barat - Maripa Annisa; Supriadi Supriadi; Nurhasnah Nurhasnah; Jasmienti Jasmienti (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
The factors that influence students' motivation to participate in extracurricular activities are the focus of this study. These factors may originate within the student (internal factors) or from without (external factors). Students' needs, hopes, and interests are all internal factors that can influence their interest in and participation in extracurricular activities. However, external factors include things like family, the natural world, and social equilibrium.This study aims to shed light on the most influential factors influencing grade eight students' decision to participate in extracurricular activities. This study combines descriptive methods with quantitative estimation. Data collection software that makes use of angkets. This study's sample population consists of the sixty-five students that participated in the pre-exam activities at Class VIII of MTsN 2 in Pasaman Barat. This study used a non-probabilistic sampling technique called "total sampling," in which the entire population was sampled because the study's population was less than 100. This study used SPSS to conduct a thorough validity test, replicability test, normality test, homogeneity test, and factor analysis on the collected data. The research results show that the factors that influence students' motivation to participate in pramuka activities at the eighth grade level at MTsN 2 Pasaman Barat are as follows: the first factor is students' expectations, with an eigen value of 4.532, or 20.601%; the second factor is students' family environments, with an eigen value of 2,453, or 11.150%; and the third factor is students' school environments, with an eigen value of 4.532. That's why hope is the most important of those other twelve factors.